2012
DOI: 10.1155/2012/762541
|View full text |Cite
|
Sign up to set email alerts
|

Review on Autoimmune Reactions in Female Infertility: Antibodies to Follicle Stimulating Hormone

Abstract: Female fertility can be affected by diseases or dysfunctions of reproductive tract, neuroendocrine system, and immune system. Reproductive autoimmune failure can be associated with overall activation of immune system or with immune system reactions specifically directed against ovarian antigens. Majority of the antiovarian autoantibodies are directed against β-subunit of follicle stimulating hormone (anti-FSH). This paper summarizes a current clinical classification of female infertility in the context of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 123 publications
(226 reference statements)
2
58
0
3
Order By: Relevance
“…Among potential causes of RIF, uterine factors (aberrant endometrial receptivity, immunological incompatibility) and embryo quality have been widely investigated [12]. Nevertheless, up to 20% of couples, whose IVF failures could not be explained by anatomic, endocrine, or chromosomal abnormalities, are determined to have “unexplained” infertility [3, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…Among potential causes of RIF, uterine factors (aberrant endometrial receptivity, immunological incompatibility) and embryo quality have been widely investigated [12]. Nevertheless, up to 20% of couples, whose IVF failures could not be explained by anatomic, endocrine, or chromosomal abnormalities, are determined to have “unexplained” infertility [3, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…With respect to age of menopause excluding POI, no convincing data supports a primary association between systemic autoimmune disorders such as lupus and rheumatoid arthritis and earlier age of menopause. Thus, autoimmune antibodies often observed in POI [120][121][122][123][124][125][126] as well as in those with incipient menopause around age 50 [127] suggests an interactive phenomenon resulting from agingrelated inflammation, immunosenescence, and hormonal changes. Additional studies are needed to ascertain the impact of autoimmunity on the onset of POI, and most importantly to assess if autoantibodies accompany rather than cause POI.…”
Section: Prenatal Nutrition Birth Weight and Early Life Exposuresmentioning
confidence: 99%
“…In studies with IVF patients, it has been suggested that strong ovulation induction causes antigen secretion and that the pick-up process, along with repeated physical trauma, causes the secretion of antigens inside of the ovarian tissue that has not encountered the immune system before [19,[23][24][25][26][27]. However, some authors argue that neither the first nor repeated cycles of IVF cause an increase in AOA concentrations [28,29]. In our study, we evaluated the effect of IVF treatment on AOA levels, by measuring the AOA in the pretreatment phase, after ovulation COH and after OPU.…”
Section: Discussionmentioning
confidence: 99%